THE ROLE OF VALUES IN NATIONAL UPBRINGING (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the role of national values in the formation of moral education of people. At the same time, the scientific theoretical literature on the place of national values in the educational process and the materials based on the practical empirical approach were analyzed. In addition, the need to implement some aspects of national values in the educational process was thoroughly studied.